Liquidity Surplus: Profitability Growth, Leverage, in Financial Service Companies - Anita, Siska Yuli; Nuraeni, Nuraeni; Moch Arif Hernawan; Siti Nurhayati; Enny Haryanti (Dinasti Publisher, 2024)
The purpose of this article is to analyze potential strategies and solutions to efficiently manage liquidity surpluses, increase profitability, and address operational issues, and provide recommendations to company management on concrete steps that can be taken to optimize liquidity surplus management, increase profitability growth, and reduce leverage and gap risks in company operations. This article uses quantitative methods, which look for influences between variables, the population in this study is middle leaders in financial companies with respondents randomly selected from several financial companies with the distribution of questionnaires. The questionnaire returned after being filled out as many as 52 respondents. Data processing in producing results from questionnaires using SPSS 23 in producing research results. Profitability and leverage have a significant influence on a company's liquidity. This suggests that a company's financial performance, such as profitability, and capital structure, such as leverage, play an important role in determining a company's liquidity level. Therefore, the company's financial management needs to pay close attention to these two factors in an effort to maintain and increase optimal liquidity levels. Pay Attention to Profitability Performance: The management of the company must continue to pay attention and improve its profitability performance. This can be done by improving operational efficiency, product innovation, and the right marketing strategy to increase company revenue and profits. It is expected that the company can maintain and increase its liquidity level, so that it can achieve its long-term financial goals more effectively and efficiently.